Students’ Perception on Characteristics of English Lecturers at Qomaruddin University - Mardiana, Dwi Syafrida; Mazidah, Eva Nur (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was conducted to find out students’ perceptions on characteristics of English lecturers. This research design was descriptive qualitative research. The subjects of this research were students of the second, fourth, and sixth semester of English Language Education Program of Qomaruddin University. It consists 74 students. The data were obtained through questionnaire (open ended and close ended) and interview. Therefore, the data were analyzed using descriptive qualitative. The results showed that students’ perceptions on characteristics of English lecturers showed percentage in every competence and it was said that almost all chose to agree with the statement given, meaning that English lecturers here are good in terms of 4 types of characteristics based on the questionnaire with pedagogical competence 57,1%, personality competence 52,6%, social competence 49,3% and professional competence 59,5%.